Geometric algorithms for conflict detection/resolution in air traffic management - Yi-Jen Chiang; Klosowski, J.T.; Changkil Lee; Mitchell, J.S.B. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
We consider the problems of conflict detection and resolution in air traffic management (ATM) from the perspective of computational geometry and give algorithms for solving these problems efficiently. For conflict resolution, we propose a simple method that can route multiple aircraft, conflict-free, through a cluttered airspace, using a prioritized routing scheme in space-time. Our algorithms have been implemented into a simulation system that tracks a large set of flights, having multiple conflicts, and proposes modified routes to resolve them. We report on the preliminary results from an extensive set of experiments that are under may to determine the effectiveness of our methods.